IMPLEMENTASI ETIKA TRANSAKSI JUAL BELI DALAM ISLAM PADA PASAR TRADISIONAL DI WATAMPONE - M. Rafid Marwal; Sri Julyanti Halid (Jurnal Ilmiah Al-Tsarwah : ilmu ekonomi dan keuangan (konvensional dan syariah), 2021)
This research is entitled the implementation of the ethics of buying and selling transactions in Islam at traditional markets in Watampone, with indicators of Islamic ethics, namely not reducing the scale or measurement, not containing elements of fraud, no coercion,khiyar, do not take perjury and prohibition on hoarding. This study aims to answer the problem of how the knowledge of sellers and buyers about the ethics of buying and selling transactions in traditional markets in Watampone and how to apply the ethics of buying and selling transactions in Islam in traditional markets in Watampone. This research is a qualitative field study using a sociological normative economic and theological approach.  The results showed; First, both sellers and buyers are mostly aware of the ethics of buying and selling transactions in traditional markets, especially in the Watampone area. Second, Islamic ethics in buying and selling transactions at traditional markets in the Watampone area have not been fully implemented, because there is still fraud or fraud in transactions. Research implication: Local government and related parties are expected to play an active role in providing counseling and supervision to sellers in traditional markets about the importance of ethics in transactions, so that the seller's knowledge of Islamic ethics in buying and selling transactions can be improved. In addition, as Muslims, after knowing about ethics in transactions, it is better if sellers and buyers can apply ethics in buying and selling transactions in accordance with Islamic law, especially in traditional markets, so that transactions are carried out not only for profit, but still get blessings. Keyword: Local Market; Ethic, Transaction; Fiqh Muamalah